The Urgency of Legal Protection for Children Involved in Drug Trafficking in Indonesia - Mursyid, Mursyid; Rishad Ilmi, Muhammad; Azham Ilham, Muhammad (Intellectual Law Review (ILRE), 2025)
This research aims to find out and analyze legal protection for children as child drug courierand to find out and analyze the factors that influence legal protection for children as child drug couriers. This research uses empirical research methods. The results of this research show that legal protection for children as child drug courieris very important, this aims to overcome the problem of criminal act and protect their future, including ensuring that they continue to have access to adequate education, and is focused on rehabilitation and social reintegration, not only punishment and the factors that influence legal protection for children as child drug courierare age, environment, education and socio-economic conditions. In addition, children who grow up in an unstable environment and are exposed to violence or criminal activities have a higher risk of falling into drug syndicates. The recommendation of this research is that it is hoped that the government will ensure that children involved as child drug courier have access to drug syndicates. proper education and comprehensive rehabilitation programs to help them get out of the cycle of criminal act and build a better future and it is hoped that security forces will process cases of child child drug courier quickly and responsibly, as well as apply an age-sensitive approach and children's special needs to ensure their rights are protected during the legal process.